2019
DOI: 10.1016/j.neuroimage.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state functional MRI studies on infant brains: A decade of gap-filling efforts

Abstract: Resting-state functional MRI (rs-fMRI) is one of the most prevalent brain functional imaging modalities. Previous rs-fMRI studies have mainly focused on adults and elderly subjects. Recently, infant rs-fMRI studies have become an area of active research. After a decade of gap filling studies, many facets of the brain functional development from early infancy to toddler has been uncovered. However, infant rs-fMRI is still in its infancy. The image analysis tools for neonates and young infants can be quite diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 208 publications
9
90
1
Order By: Relevance
“…Globally, our findings are in accordance with results from prior research based on histology, structural and rest functional brain imaging that has revealed distinct maturation trajectories of cortical regions and brain networks over the first year of life (10, 24, 33, 50). Firstly, at the histological level, post-mortem data showed that the time course of synaptogenesis differs across cortical regions.…”
Section: Discussionsupporting
confidence: 92%
“…Globally, our findings are in accordance with results from prior research based on histology, structural and rest functional brain imaging that has revealed distinct maturation trajectories of cortical regions and brain networks over the first year of life (10, 24, 33, 50). Firstly, at the histological level, post-mortem data showed that the time course of synaptogenesis differs across cortical regions.…”
Section: Discussionsupporting
confidence: 92%
“…Although only segmentations of relatively high quality were used, these segmentations were still of low quality relative to segmentations produced from structural images in adults and older children; this is perhaps not surprising as the cortex of an infant's brain is thin and the contrast between gray and white matter is low. The difficulty of infant segmentation is well known (Makropoulos et al, 2016) and acknowledgment of this has led to nonconformity in infant segmentation pipelines (Makropoulos et al, 2018;Zhang et al, 2019). With regard to anthropometry, infant weight, for instance, can vary considerably depending on quantities eaten and recency of quantities expelled.…”
Section: Discussionmentioning
confidence: 99%
“…3A) were submitted to the FreeSurfer recon-all pipeline for infant MRI images (Zöllei et al, 2017) and subject data. It should be noted that there is still no consensus regarding the best segmentation pipeline for infant imaging (Makropoulos et al, 2018;Zhang et al, 2019).…”
Section: Mri Pre-processingmentioning
confidence: 99%
“…Deformable Registration via Attribute Matching and Mutual‐Saliency Weighting (DRAMMS) (Ou, Sotiras, Paragios, & Davatzikos, ) was used as part of registering atlas and subject data. It should also be noted, however, that there is still no consensus about the segmentation pipeline for infant imaging (Makropoulos, Counsell, & Rueckert, ; Zhang, Shen, & Lin, ). These segmentations were subsequently consolidated into gray matter (GM), white matter (WM), and cerebrospinal fluid (CSF) regions‐of‐interest (ROIs) for each participant using in‐house MATLAB 2015b ( MathWorks ) code.…”
Section: Methodsmentioning
confidence: 99%